Offline impact of transcranial focused ultrasound on cortical activation in primates - Verhagen, Lennart; Gallea, Cécile; Folloni, Davide; Constans, Charlotte; Jensen, Daria EA; Ahnine, Harry; Roumazeilles, Léa; Santin, Mathieu; Ahmed, Bashir; Lehericy, Stéphane; Klein-Flügge, Miriam C; Krug, Kristine; et al. (eLife, 2019)
To understand brain circuits it is necessary both to record and manipulate their activity. Transcranial ultrasound stimulation (TUS) is a promising non-invasive brain stimulation technique. To date, investigations report short-lived neuromodulatory effects, but to deliver on its full potential for research and therapy, ultrasound protocols are required that induce longer-lasting ‘offline’ changes. Here, we present a TUS protocol that modulates brain activation in macaques for more than one hour after 40 s of stimulation, while circumventing auditory confounds. Normally activity in brain areas reflects activity in interconnected regions but TUS caused stimulated areas to interact more selectively with the rest of the brain. In a within-subject design, we observe regionally specific TUS effects for two medial frontal brain regions – supplementary motor area and frontal polar cortex. Independently of these site-specific effects, TUS also induced signal changes in the meningeal compartment. TUS effects were temporary and not associated with microstructural changes.
Keywords: brain stimulation; transcranial ultrasound stimulation; neuroimaging; resting-state fMRI; connectivity; frontal lobe